Analisis Puisi Siapakah Engkau, Corona Karya Marhalim Zaini dengan Menggunakan Pendekatan Mimetik - Romadon, Mochammad Muchlis (Varied Knowledge Journal, 2024)
As the Covid-19 situation gradually becomes more manageable with the implementation of new adaptations and the availability of vaccines provided by the government, society has begun to adapt. Throughout the pandemic, although social activities have been restricted, it has not limited the creation of literary works, including poetry that emerged amidst the Covid-19 pandemic. One such poem titled "Who are you, Corona" has emerged, becoming a work that vividly portrays the atmosphere during the Covid-19 pandemic. Researchers utilized a qualitative approach and employed the mimetic method to analyze the poem. The results of the analysis provide a realistic depiction of the human condition amidst the Covid-19 pandemic. There are four main points highlighted in the analysis, one of which is "Silent Operations and Bullets of Anxiety," conveying the author's message by comparing the spread of the Covid-19 virus to a silent military operation that instills anxiety and fear worldwide.